Pharmacologic Therapy for Erectile Dysfunction and its Interaction With the Cardiovascular System. (January 2014) - Ioakeimidis, Nikolaos; Kostis, John B.
Phosphodiesterase (PDE) enzymes are widely distributed throughout the body, having numerous effects and functions. The PDE type 5 (PDE5) inhibitors are widely used to treat erectile dysfunction (ED). Recent, intense preclinical and clinical research with PDE5 inhibitors has shed light on new mechanisms and has revealed a number of pleiotropic effects on the cardiovascular (CV) system. To date, PDE5 inhibition has been shown to be effective for the treatment of idiopathic pulmonary arterial hypertension, and both sildenafil and tadalafil are approved for this indication. However, current or future PDE5 inhibitors have the potential of becoming clinically useful in a variety of CV conditions such as heart failure, coronary artery disease, and hypertension. The present review discusses recent findings regarding pharmacologic treatment of ED and its interaction with the CV system and highlights current and future clinical applications beyond ED.